The Reflectivity of Feedback and Its Impact on Retaining Learning Outcomes - بابان, وليد خالد عبدالكريم (Sulaimani Journal for Humanities, 2019)
The aim of the current research is to identify the effect of the test reflection on the retention of learning outcomes among the students of the fourth stage in the faculties of education. The final sample was 93 students, 49 students in the experimental group and 44 students in the control group. Before analyzing the results of the test, the two groups were statistically equal in the previous information test. Excluding the results of students who failed in the previous year on the results of their colleagues (non-repeaters). The topics to be studied in the experiment were identified and their behavioral objectives were formulated in the light of general objectives and subject content. After that, the researcher prepared a collection test in the measurement and evaluation material, the researcher proves its psychometric properties and applied it to the students of the two research groups at the end of the experiment, which lasted for a full semester. After the analysis of the data using the T-test for two independent samples, the researcher found that there were statistically significant differences between the achievement of the students of the two groups at the level of (0.05) for the benefit of the students of the experimental group and using the Eta squard η2 to determine the effect of the test in raising the experimental group, There is a strong impact of the test in raising the scores of the experimental group because of the news of their members with the pattern of the test they received in advance. The results showed that the effect of the independent variable, which is the students' news of the test pattern, was that the value of the effect size was low in the follow-up test, which was conducted three months after the first test. The pre-test knowledge of the experimental group, High in the post- test, these grades were reversed and recorded a decline in the sequential test, unlike the control group that was not reported by the test pattern, and retained the learning outcomes. From these results, the researcher concluded that the prior knowledge of the test pattern is reflected in learning and leads to an increase in grades because the students will adapt their experience with the pattern of the test they will undergo. However, these grades will tend to decrease later due to their lack of learning outcomes. The test pattern will prepare students to study in a way that fits all the test patterns they are likely to encounter in the achievement test, which means they will be more retention-oriented than if they were informed by the test pattern. In order to complete this research, the researcher suggested conducting studies on the impact of test-based tests on learning outcomes.
Keywords: Wash Back; test; learning outcomes